Activity of trypsin inhibition by protein extracts from Squalus acanthias - Roșoiu, Natalia; Șerban, Mihai; Panait, Maria (Cercetări Marine - Recherches Marines, 2026)
Protein extracts from viscera of Squalus acanthias develop trypsin inhibition activity comparable to that of the natural inhibitors separated and purified from pancreas, fowl eggs and soya. Thus, a quantity of only 0.10 mg of raw natural inhibitor extracted from shark viscera inhibits by 25% the enzymatic activity of 6 mg of pure trypsin (Merck).